Development of Entrepreneurship Model for Elderly. - Suharti Suharti; Sri Iswanti; Agus Triyanto (Jurnal Penelitian Humaniora, 2018)
This study was aimed at producing entrepreneurial models for elderly people and determining the obstacles encountered in their development. This study used a Development Research approach. Research location in the Special Region of Yogyakarta. Sources of research data were elderly and Elderly Family Development Program members who have creative economic ventures. The research data was collected by observation, interviews and Focus Group Discussion methods. Data analysis was carried out by qualitative analysis. The validity of the data used triangulation methods and sources. The results show that there were four draft models used at the study site. The first model is the business model carried out by the elderly together with their family members. Second, the elderly was in charge of finding raw materials, then the elderly and Elderly Family Development personnel sell these products to neighbors and the general public. Third, the business model carried out by the elderly who are still healthy and strong, productive economic efforts. The fourth model is a joint business model.Pengembangan Model Kewirausahaan bagi Insan Lanjut UsiaPenelitian ini sampai pada tahap kedua bertujuan untuk menghasilkan model kewirausahaan bagi insan lanjut usia dan mengetahui hambatan-hambatan yang ditemui dalam pengembangannya. Penelitian ini menggunakan pendekatan Penelitian Pengembangan. Lokasi penelitian di Daerah Istimewa Yogyakarta. Sumber data penelitian adalah para lanjut usia dan anggota BKL yang memiliki usaha ekonomi kreatif. Data penelitian dikumpulkan dengan metode observasi, wawancara dan Focus Group Discussion. Analisis data dilakukan dengan analisis kualitatif. Keabsahan data menggunakan triangulasi metode dan sumber. Hasil penelitian menunjukkan ada empat draf model yang digunakan di lokasi penelitian. Model pertama, model usaha yang dilaksakan para lansia bersama-sama dengan anggota keluarganya. Kedua, lansia bertugas mencari bahan baku, lansia, dan BKL menjual produk tersebut kepada tetangga dan masyarakat umum. Ketiga, model usaha yang dilaksanan oleh lansia yang masih sehat dan kuat, usaha ekonomi produktif. Model keempat adalah model usaha gabungan.